Ответы и объяснения

  • Minsk00
  • почетный грамотей
2013-07-20T00:56:46+00:00
(0,5x+1,2)-(3,6-4,5x)=(4,8-0,3x)+(10,5x+0,6)
Раскрываем скобки
0,5x+1,2-3,6+4,5x=4,8-0,3x+10,5x+0,6
Приводим подобные члены
x(0,5+4,5)+1,2-3,6=4,8+0,6+x(10,5-0,3)
5x-2,4=5,4+10,2x
10,2x-5x = -2,4-5,4
5,2x=-7,8
x=-78/52=-1,5
Ответ -1,5
  • AlbuRin
  • светило науки
2013-07-20T01:14:22+00:00
(0.5x +1.2) - (3.6 - 4.5x) = (4.8 - 0.3x)  + (10.5x + 0.6)
0.5x + 1.2 - 3.6 + 4.5x = 4.8 -0.3x + 10.5x + 0.6
5x - 10.2x  = 5.4 + 2.4
-5.2x = 7.8
x = -7.8/5.2
x = -1.5